Uma investigação acerca da evolução do momentum angular em sistemas planetários - Rosa, Francisco Daniel de Carvalho (2021)
Research on stellar and planetary angular momentum has generated numerous works in recent decades. These researches are based on the relationship between spin angular momentum and stellar mass, but this relationship changes when analyzing systems with and without planets. In the present work, we investigate this relationship based on a sample of 578 stars with and without planets at different evolutionary stages. As a result, we observed that stars that host planets show a deficit of spin angular momentum when compared to those that do not have planets, this result persists even for those that have already left the main sequence. We believe this is because, in planetary systems, the host star loses much of its angular momentum to the planets just as it does in the Solar System. Another result is that the rates of J_{\star} (stellar angular momentum), J_{p} (planetary angular momentum) and J_{tot} (total angular momentum) are influenced by the methods used for discoveries of exoplanets, therefore, each technique has unique peculiarities in the act of computing the angular momentum. Furthermore, when we analyze the ratio beteween the planetary and total angular momentum, we find that exoplanets detected by radial velocity retain higher concentrations of J_{tot} than those discovered by transit. Thus, with the present research we were able to know the behavior of angular momentum rates for main sequence stars and evolved branches and how the presence of planets interferes in these values.